Novapus bifidus Carne, 1957, a primary homonym and synonym of Novapus bifidus Lea, 1910 (Coleoptera: Scarabaeidae: Dynastinae) - Allsopp, Peter G.; Hudson, Peter J. (Zootaxa, 2019)
In his landmark revision of the Australian Dynastinae (Coleoptera: Scarabaeidae) Phil Carne (1957) described Novapus bifidus Carne, 1957 from males and females collected at Cape York and Thursday Island. The type series is in the Australian National Insect Collection, Canberra, Australia (ANIC); the Natural History Museum, London, United Kingdom; the South Australian Museum, Adelaide, Australia (SAM); and the Museum of Victoria, Melbourne, Australia. He noted “In the collections of the South Australian Museum there are specimens designated as types of bifidus Lea. No description of this species has been published, and it is now described under the same specific name”. One of his paratypes is a female in SAM identified as “Lea’s unpublished ♀ type” and two other paratypes are males in SAM. Cassis & Weir (1992) noted that one of the SAM specimens has the registration number I4268, although they knew of only two paratypes (one male, one female) in that collection. The name has been attributed to Carne by most subsequent authors (Endrődi 1974, 1985; Carne & Allsopp 1987; Cassis & Weir 1992; Dechambre 2005; Atlas of Living Australia 2018.). Krajcik (2005, 2012) listed it in his scarab checklists but as “bifidus? Carne 1957”.